Performance payments: A new strategy to conserve large carnivores in the tropics? - Astrid Zabel; Stefanie Engel (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Biodiversity, including wildlife, is globally decreasing at alarming rates. This development has evoked calls for innovative conservation policies. In the present paper we explore the novel conservation performance payment approach which for wildlife-livestock conflicts, so far, has only been implemented in Sweden. The contribution of the paper is twofold. A structural framework of performance payments' design is developed and an empirical assessment of the approach to tiger-livestock conflicts at Bandhavgarh National Park in India, an example where conservation needs compete with humans' increasing demand for land and resources, is presented. The framework focuses on issues of scheme design such as identifying performance indicators, targeting, payment amount and timing, considerations on making payments to groups vs. individuals, scheme duration, and inadvertent side effects. The assessment of the applicability of the performance payment approach to tiger (Panthera tigris) conservation is based on a high-profile policy workshop, an interview with the park management, and 305 household-level interviews conducted in 20 villages in the buffer zone of the park.
Keywords: Q20; 330; Conservation performance payments; Payments for environmental services; Wildlife-livestock conflicts; India; Sweden